Hikmah Zakat dalam Perspektif Hukum Islam: Analisis Filosofis atas Relasi Manusia, Harta, dan Tuhan - Muhammad Nazim Aldiansyah; Rahma Alya Purwanto (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This study is motivated by the urgency to understand the wisdom of zakat not merely as a ritual obligation, but as a philosophical construct that reflects the integral relationship between human beings, wealth, and God within the framework of Islamic law. The growing practice of zakat, supported by national collection data, illustrates complex theological and socio-economic dynamics that require deeper examination to prevent its meaning from being reduced to a simple act of charity. This research employs a qualitative-descriptive method through an analysis of classical fiqh literature, Indonesia’s regulatory framework on zakat, and official BAZNAS reports, all of which are interpreted using philosophical and Islamic legal approaches. The findings reveal that zakat embodies multifaceted wisdom, including self-purification, the affirmation of ethical ownership, and the restoration of social justice through structured wealth distribution. The analysis further highlights that strengthening zakat management systems both normatively and institutionally serves as a crucial foundation for reinforcing the relationship between spiritual obligations and public welfare in accordance with the principles of Islamic law.